Gil Evans : out of the cool : his life and music - Stein Crease, Stephanie (A cappella, 2002)
The life (1912-1988) and career of Gil Evans paralleled and often foreshadowed the quickly changing world of jazz through the 20th century. Gil Evans: Out of the Cool is the comprehensive biography of a self-taught musician whom colleagues often regarded as a mentor. His innovative work as a composer, arranger, and bandleaderfor Miles Davis, with whom he frequently collaborated over the course of four decades, and for his own ensemblesplaces him alongside Duke Ellington and Aaron Copland as one of the giants of American music. His unflagging creativity galvanized the most prominent jazz musicians in the world, both black and white. This biography traces Evans's early years: his first dance bands in California during the Depression; his life as a studio arranger in Hollywood; and his early work with Claude Thornhill, one of the most unusual bandleaders of the Big Band Era. After settling in New York City in 1946, Evans's basement apartment quickly became a meeting ground for musicians. The discussions that took place there among Miles Davis, Gerry Mulligan, John Lewis, and others resulted in the Birth of the Cool scores for the Miles Davis Nonet and, later on, for Evans's masterpieces with Davis: Miles Ahead, Porgy and Bess, and Sketches of Spain. This replaces 1556524250.